Análise de assunto de conto espírita por meio do percurso figurativo e do percurso temático - Damazo, Alessandra Cristina [UNESP] (2006)
In the field of Knowledge Organization, more specifically in the approach of information usage, there is a lack of theorical assistance concerning to the analysis of fictitious documents. Trying to theorically contribute with the development of a method that makes easier the analysis of subjects in a narrative text, on its aspects of identification and selection of concepts, we researched theorical assistance in interface fields linked to the Science of Knowledge, more specifically Linguistics. This last one provided the Knowledge about the textual structure into the narrative text and the Discursive Semantics contributed with the thematic and figurative courses, used as tools on the analysis of questions form narrative texts. We aimed, therefore, the formulation of a method that could make easier the task of analyzing the subject, its aspects of identification and selection of concepts, in order to foment the accessibility of the content into the document. To achieve it, we opted by the analysis of there spiritualistic tales, in which was initially identified, on its structures, the canonic sequence and, through it, we did the analysis of the thematic and figurative paths, due to the identification of the concepts. The results were the identification of primary and secondary themes in the narrative texts that were analyzed. From it, we concluded that the experimental method of analysis proposed was efficient into the corpus of this research, because allowed us the identification of relevant concepts that characterize the issues approached in the tales, which will, in the future, be translated into a language from the system of information. We still suggest the development of a review to verify and hold true the hypothesis that appeared during this paper, and it states that in levels of Manipulation and Sanction, elements to the canonic sequence... (Complete abstract, click electronic address below)